Circulating Cell-Free DNA in Plasma of Locally Advanced Rectal Cancer Patients Undergoing Preoperative Chemoradiation: A Potential Diagnostic Tool for Therapy Monitoring. Issue 3 (4th June 2013) - Zitt, Matthias; Müller, Hannes M.; Rochel, Marina; Schwendinger, Verena; Zitt, Marion; Goebel, Georg; DeVries, Alexander; Margreiter, Raimund; Oberwalder, Michael; Zeillinger, Robert; Öfner, Dietmar
Abstract : Circulating cell-free DNA opens up an interesting field for therapy monitoring, in particular during multimodal therapy protocols. The objective of this proof of principle study was to evaluate whether the amount of circulating plasma DNA has the potential to serve as a marker for therapy monitoring during the treatment course of locally advanced rectal cancer patients. We especially focused on kinetics of circulating DNA to assess whether variances in kinetics have the potential to discriminate between therapy responders and nonresponders. The amount of circulating DNA in plasma of rectal cancer patients undergoing preoperative chemoradiation was determined using real-time PCR before chemoradiation, after the end of chemoradiation and at the end of treatment. The study population was divided into responders (ypT0-T2 stage) and nonresponders (ypT3-T4 stage). Both groups showed comparable median plasma DNA values before and after the end of chemoradiation. At the end of treatment responders showed a further decrease in circulating DNA, whereas in nonresponders the circulating DNA manifestly increased (P = 0.006). This study demonstrates that circulating DNA in plasma of rectal cancer patients undergoing preoperative chemoradiation might serve as a surrogate marker to discriminate between responders and nonresponders. Therefore, we hypothesize that quantification of plasma DNA could be of use as an easily accessible tool for therapy monitoring in these patients.